The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/interface.190441
|View full text |Cite
|
Sign up to set email alerts
|

Aproximação dialógica às necessidades de saúde em usuários de insulina acompanhados no Programa de Automonitoramento Glicêmico

Abstract: O presente estudo busca caracterizar, a partir de pesquisa qualitativa, as ações de profissionais da Atenção Básica à Saúde (ABS) atuantes no Programa de Automonitoramento Glicêmico (PAMG), com vistas à troca de saberes possibilitada pelo encontro com pessoas em uso de insulina cadastradas no programa. Selecionaram-se 12 usuários para realização de rodas de conversa e foram conduzidas entrevistas semiestruturadas com os trabalhadores atuantes no PAMG, em uma Unidade Básica de Saúde (UBS) da capital paulista. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…The sociodemographic characteristics of the users who validated this PEM showed a profile of people with a time since diagnosis similar to that of other research studies 25,34 . The insulin pen use time, which was 9.8 years in this research, can be associated with more people diagnosed with type 1 DM, something that has also been identified in other studies [34][35][36] .…”
Section: Stage 3 Results -Validation Of the Pem With Userssupporting
confidence: 79%
See 1 more Smart Citation
“…The sociodemographic characteristics of the users who validated this PEM showed a profile of people with a time since diagnosis similar to that of other research studies 25,34 . The insulin pen use time, which was 9.8 years in this research, can be associated with more people diagnosed with type 1 DM, something that has also been identified in other studies [34][35][36] .…”
Section: Stage 3 Results -Validation Of the Pem With Userssupporting
confidence: 79%
“…In fact, the application technique with the insulin pen can be complex, mainly for older adults and/or those with low schooling levels 24 . Added to this, the difficulty understanding technical knowledge and the therapeutic protocol is seen as a barrier to adhering to the DM treatment 25 . In this sense, while preparing the PEM, it was decided to use photographs of all the components that govern the application technique, in order to illustrate the procedure and make it more familiar, intuitive and easy to understand -which corroborated with the users' expectations.…”
Section: Stage 3 Results -Validation Of the Pem With Usersmentioning
confidence: 99%
“…In line with these results, a study conducted in São Paulo, Brazil, found that the materials used in insulin therapy are related to therapeutic compliance and that insulin pens are an excellent alternative to facilitate adherence. Conversely, there may be barriers to insulin administration when it requires different materials for storage and transportation or when feelings such as fear, insecurity, and pain are aroused by the route of administration (Dias & Junqueira, 2020). Bariya and Nayberg (2017) from the University of California also emphasized the benefits of replacing the syringe with the insulin pen to minimize the burden on management and enable better performance, given that syringes are associated with pain, inconvenience, and social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…O acesso às necessidades de saúde das pessoas com DM depende da troca efetiva de saberes entre profissionais de saúde e usuários do sistema, capaz de superar a transmissão passiva e a hierarquização de conhecimentos técnicos frequentemente presentes nos encontros assistenciais. Explorá-las sob o dialógico é fundamental para a prática do cuidado integral, capaz de compreender o indivíduo portador de DM em seu todo existencial e, consequentemente, considerar os obstáculos que devem ser superados para a reordenação dos seus modos de vida 6,7 .…”
Section: ____________________unclassified